Hegel's encyclopedic system
1 online resource.
Keywords: "This book discusses the most comprehensive of Hegel's works: his long-neglected Encyclopedia of the Philosophical Sciences in Outline. It contains original essays by internationally renowned and emerging voices in Hegel scholarship. Their contributions elucidate fundamental aspects of Hegel's encyclopedic system with an eye to its contemporary relevance. The book thus addresses system-level claims about Hegel's unique conceptions of philosophy, philosophical "science" and its method, dialectic, speculative thinking, and the way they relate to both Hegelian and contemporary notions of nature, history, religion, freedom, and cultural praxis"--